Active carbon prepared from vegetable wastes for the treatment of Pb(II) in aqueous medium (Bangladesh Journal of Scientific and Industrial Research, 2013)
Activated carbon was prepared from vegetable wastes collected from the residential halls of University of Dhaka, Bangladesh. The carbon, produced by pyrolysis of vegetable wastes at 400°C to 600°C for 30 min under N2 atmosphere, was chemically activated with zinc chloride. The activated carbon samples were characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR). Topographical and morphological characteristics were examined by Scanning Electron Microscopy (SEM). The surface area of the activated charcoal was determined by adsorption of Methylene Blue from alcoholic solution and was found to be 53 m2g-1. The zero point charge (pHzpc) was also determined by pH titration means and obtained to be 6.10±0.1 at ambient temperature. Analyses of these experimental data lead us to conclude that the activated carbon prepared from vegetable wastes materials is a high grade active carbon in comparison with commercially available one. Activity of generated active carbon as an adsorbent was tested through adsorption of Pb(II). The results indicate that adsorption of Pb(II) on active charcoal was very fast and it followed Langmuir type of adsorption isotherm, and the dimensionless separation parameter, RL, was found to be 0